Synthesis and properties of ascorbyl esters catalyzed by lipozyme TL im using triglycerides as acyl donors - Reyes-Duarte, Dolores; López-Cortés, Nieves; Torres, Pamela; Comelles, Francesc; Parra, J.L.; Peña, S.; Ugidos, A.V; Ballesteros Olmo, Antonio; Plou Gasca, Francisco José (Journal of the American Oil Chemists' Society, 2011)
[EN] Esters of l-ascorbic acid with long-chain fatty acids (E-304) are employed as antioxidants in foods rich in lipids. Although their enzymatic synthesis offers some advantages compared with the current chemical processes, most of the reported methods employ the immobilized lipase from Candida antarctica as biocatalyst and free fatty acids or activated esters as acyl donors. In order to diminish the cost of the process, we have investigated the synthesis of ascorbyl oleate and ascorbyl palmitate esters with the immobilized Thermomyces lanuginosus lipase Lipozyme TL IM-which is significantly less expensive than Novozym 435-and triglycerides as source of fatty acids. Lipozyme TL IM gave rise to a lower yield of 6-O-ascorbyl oleate than Novozym 435 when using triolein (64 vs. 84%) and olive oil (27 vs. 33%) as acyl donors. Both 6-O-ascorbyl oleate and 6-O-ascorbyl palmitate displayed excellent surfactant and antioxidant properties. The Trolox Equivalent Antioxidant Capability values for the oleate and palmitate were 71 and 84%, respectively, of those obtained with l-ascorbic acid; however, both derivatives were able to stabilize soybean oil towards peroxide formation. © 2010 AOCS. Comunidad de Madrid for a research contract to P. Torres and to CONACYT for grant 020256 to D. Reyes. This research was supported by the Spanish CSIC (Project 200680F0132) and by the Latin-American Science & Technology Development Programme (CYTED Project 108RT0346).